Dynamics of the modified exponential model inspired by scalar and Maxwellian field - Разина , О. В.; Нуржау , Н. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The authors have investigated f(R) - gravity with a Maxwell-type field and k-essence using a homogeneous isotropic and flat Friedman - Robertson - Walker Universe. The authors have found the equations of motion for this model, calculated the solution for the scale factor and the function of the scalar field, as well as for the potential of the scalar field. The article identifies the dark energy density and pressure, investigated the parameters of slow rolling. For this model, the slope and curvature of the potential, otherwise called slow roll-off parameters, satisfy the condition for inflation to occur. Our model allows us to obtain the accelerated expansion of the Universe during the period of inflation. Over time, the field decreases, slowly decreases, and the Universe comes out of the inflationary regime, which demonstrates the exponential dynamics of changes in the law of expansion of the Universe.